Sistem Informasi Manajemen Persediaan Stock Barang pada Toko Shaqi Bakery Menggunakan Metode Enterprise Resource Planning Berbasis Web - Nugraha, Muhammad Reza; Suendri, Suendri (Program Studi Teknik Informatika Universitas Pamulang, 2024)
The advancement of technology has provided opportunities to process and utilize information with high speed, accuracy, and effectiveness. With the evolution of technology, activities that were once time-consuming, costly, and labor-intensive have become very practical and efficient. Shaqi Bakery continued to employ manual methods, resulting in ineffective and inaccurate inventory stock calculations. In response to this challenge, the implementation of computerized information systems such as ERP became necessary. By utilizing ERP, Shaqi Bakery could enhance the efficiency of its stock management. The objective of this system was to address the risk of human errors in stock data recording, thus ensuring accurate information retrieval. Integrating ERP modules into the Management Information System made detailed stock calculations easier for users at Shaqi Bakery's facility. The development method employed was the Rapid Application Development (RAD) methodology. Its purpose was to minimize existing issues and enhance consumer security.